2012
DOI: 10.1186/1866-1955-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, reliability, and clinical validity of the Test of Attentional Performance for Children (KiTAP) in Fragile X syndrome (FXS)

Abstract: BackgroundAttention and inhibition are core executive-function deficits in FRagile X syndrome (FXS). This pilot study evaluated the feasibility, reproducibility, and clinical relevance of the KiTAP, a computer-based pictorial measure of attention and inhibition with an enchanted-castle theme, in an FXS cohort.MethodsThe 8-subtest KiTAP battery (as many subtests as each could perform) was given to 36 subjects with FXS, of variable age and cognitive/behavioral functioning, and 29 were retested, with an interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 29 publications
1
60
1
Order By: Relevance
“…Based on our prior work on the feasibility, reliability, and validity of the KiTAP in FXS [49], we chose the flexibility, go/no-go, and distractibility subtests, which include reliable and validated scores matching well with several NIH-TCB constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our prior work on the feasibility, reliability, and validity of the KiTAP in FXS [49], we chose the flexibility, go/no-go, and distractibility subtests, which include reliable and validated scores matching well with several NIH-TCB constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Only a subset of outcome measures utilized in recent trials have shown good feasibility and validity (Berry-Kravis et al 2006, 2008a, b, 2009). Thus, recently investigators have begun to develop templates for pretrial feasibility, reproducibility, and validity assessment (Berry-Kravis et al 2008a, b; Hessl et al 2008; Knox and Berry-Kravis 2009; Scaggs et al 2011). The choice of outcome measures must also balance the use of standard accepted behavioral measures with precedent for use in drug registration/FDA approval, which are generally caregiver rating scales (such as the ABC), versus use of novel measures (Hessl et al 2008; Knox and Berry-Kravis 2009; Scaggs et al 2011) that are more quantitative and may objectively measure core phenotypes (such as eye tracking or PPI), thus advancing treatment science, but have no precedent for registration and are not yet known to predict a specific functional outcome.…”
Section: 1 Introductionmentioning
confidence: 99%
“…Only a subset of outcome measures utilized in recent trials have turned out to fulfill the majority of these criteria (Berry-Kravis et al, 2006) suggesting better, FXS-specific measures are needed. Only recently have investigators begun to develop templates to test the feasibility, reproducibility, and validity assessment before using the measure in a trial (Berry-Kravis et al, 2008b;Hessl et al, 2009;Knox and Berry-Kravis, 2009;Farzin et al, 2011). Choice of outcome measures must also balance use of accepted behavioral measures, which are generally caregiver rating scales (such as the ABC), with precedent for use in drug registration/FDA approval versus use of novel measures Knox and Berry-Kravis, 2009;Farzin et al, 2011) that are more quantitative and may objectively measure core phenotypes and electrophysiology (such as eye tracking or PPI).…”
Section: Trial Design and Hurdles Identified In Early Clinical Trialsmentioning
confidence: 99%
“…Only recently have investigators begun to develop templates to test the feasibility, reproducibility, and validity assessment before using the measure in a trial (Berry-Kravis et al, 2008b;Hessl et al, 2009;Knox and Berry-Kravis, 2009;Farzin et al, 2011). Choice of outcome measures must also balance use of accepted behavioral measures, which are generally caregiver rating scales (such as the ABC), with precedent for use in drug registration/FDA approval versus use of novel measures Knox and Berry-Kravis, 2009;Farzin et al, 2011) that are more quantitative and may objectively measure core phenotypes and electrophysiology (such as eye tracking or PPI). These novel quantitative measures advance treatment science, but have no precedent for registration, do not clearly predict a specific functional outcome, and are often expensive and difficult to run at multiple sites.…”
Section: Trial Design and Hurdles Identified In Early Clinical Trialsmentioning
confidence: 99%